O comércio de “couro dourado”/guadameci entre Córdova e Lisboa: um contrato de venda de 1525 - Franklin Pereira (Medievalista)
“The trade of gilt leather/guadameci between Córdoba and Lisbon: a contract from 1525” deals with a document of imports between a gilt leather maker from Lisbon, working for the court, and a painter from Córdoba; the list includes altar fronts, wall hangings and cushions. Besides commenting such contract, the author refers the uses of gilt leather in both Iberian countries coming out of the Reconquest as part of the mudejar fashions of the 15th-16th centuries.